2010
DOI: 10.4021/wjon223w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Response to Neoadjuvant Anthracycline Based Chemotherapy in women with breast cancer

Abstract: BackgroundNeoadjuvant chemotherapy has been used as a primary treatment for locally advanced or inflammatory breast cancer, and recently extended to operable breast cancer. The aim of this study was to evaluate the predictive value of different histologic factors in breast cancer treated with neoadjuvant anthracycline chemotherapy in Tunisian women.MethodsA total of 109 stage II and III breast cancer patients who received neoadjuvant anthracycline chemotherapy were enrolled in this study. Using pretreatment bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
3
1
0
Order By: Relevance
“…While comparing with another study, complete clinical response in our study (26.6%) was comparable with Alvarado et al, 19 which showed a cCR of 12%, and Garbhi olfa et al, 20 which showed a cCR of 14%. The partial response rate in our study was 50%.…”
Section: Discussionsupporting
confidence: 89%
“…While comparing with another study, complete clinical response in our study (26.6%) was comparable with Alvarado et al, 19 which showed a cCR of 12%, and Garbhi olfa et al, 20 which showed a cCR of 14%. The partial response rate in our study was 50%.…”
Section: Discussionsupporting
confidence: 89%
“…In this study we have analysed the incidence of pCR to neoadjuvant chemotherapy and chemoradiation in our patient population. In various studies, incidence of pCR ranges from 12-30% in anthracycline based therapy [6]. The pCR rate in this study (14.4%) is comparable to other published series using anthracycline based chemotherapy [6,7,8] .…”
Section: Statistics Analysissupporting
confidence: 75%
“…In various studies, incidence of pCR ranges from 12-30% in anthracycline based therapy [6]. The pCR rate in this study (14.4%) is comparable to other published series using anthracycline based chemotherapy [6,7,8] . In a study by Prisack et al [9] pCR was seen more frequent in tumors that received radiochemotherapy (28.3%) compared to chemotherapy alone (11.9%).We also noticed a higher pCR in neoadjuvant chemoradiation (23%) though the sample size is not comparable.…”
Section: Statistics Analysissupporting
confidence: 75%
“…Pathological complete response is one of the important predicting long time survival in Post NACT patients. The pathological complete response rates varied from 8-30% in various anthracycline based regimens (8)(9)(10)(11)(12) . In the present study the pathological complete response was observed in 42 out of 108 cases constituting 39%.we did find one study with a higher pathological complete response of 40%.…”
Section: Discussionmentioning
confidence: 99%